Distribution of Ocular Anterior and Posterior Segment Lengths Among a Cataract Surgical Population in Shanghai - Qi, Jiao; He, Wenwen; Meng, Jiaqi; Wei, Ling; Qian, Dongjin; Lu, Yi; Zhu, Xiangjia (Frontiers in Medicine, 2021)
Purpose To investigate the distributions of the ocular anterior and posterior segment lengths among a cataract surgical population in Shanghai. Design Cross-sectional study Methods Ocular biometric parameters of 23462 eyes of 23462 cataract surgery candidates were reviewed. Axial length (AL), anterior chamber depth (ACD) and lens thickness (LT) were obtained using IOL Master. Anterior segment length (ASL = ACD + LT), posterior segment length (PSL = AL - ASL) and the ratio of ASL to PSL (ASL/PSL) were calculated. Results: The mean ASL was 7.58 ± 0.39 mm, the mean PSL was 17.12 ± 2.64 mm. As the age grew, the ASL increased, and PSL increased firstly then decreased. Male subjects tended to have significantly longer ASL and shorter PSL than female subjects. With the increasing AL, the ASL was firstly decreased to trough at 20-22 mm AL group, then increased gradually, while the PSL increased rapidly. The ASL correlated positively with AL in normal, moderate and highly myopic eyes, negatively in short eyes. The PSL correlated positively with AL across the entire study population. The ASL/PSL was not constant in the eyes with different AL but had a relatively steep downward trend with the increasing AL in the short eyes, then decreased smoothly in normal, moderate and highly myopic eyes. Conclusions: In Chinese cataractous eyes, longer ASL and shorter PSL were associated with elder age and male gender. The change of ASL over AL was not linear, and the ASL was smallest in the eyes with AL of 20 to 22 mm. The elongation of the eyeball was mainly due to the extension of the posterior segment.